Cyclic long-term loading of a bilateral fixed-angle plate in comparison with tension band wiring with K-wires or cannulated screws in transverse patella fractures - Thelen, Simon; Schneppendahl, Johannes; Baumgaertner, Ralf; Eichler, Christian; Koebke, Juergen; Hakimi, Mohssen; Windolf, Joachim; Wild, Michael; Betsch, Marcel (Knee Surgery Sports Traumatology Arthroscopy, 2013)
Purpose: A bilateral fixed-angle plate was biomechanically compared to the two currently preferred methods of osteosynthesis for transverse patella fractures. It was hypothesized that the new angle-stable implant would provide a secure and sustainable fracture fixation, superior to the established standard techniques. Methods: Twenty-one identical patellae made of polyurethane foam (Sawbones®), osteotomized to create a transverse two-part fracture, were fixed with modified anterior tension wiring, cannulated lag screws with anterior tension wiring or bilateral polyaxial 2. 7-mm fixed-angle plates. The testing protocol consisted of 10,000 repetitive cycles using a non-destructive physiological load between 100 and 300 N at a simulated knee flexion of 60°. Results: All 21 Sawbone®-patellae sustained repetitive loading up to 10,000 cycles without failing. The anterior tension wire group displayed significant displacement of the fracture gap (0. 7 ± 0. 2 mm) during cyclic loading, while both lag screws with tension wiring and bilateral fixed-angle plates showed no fracture gap widening at all (p < 0. 01). Conclusion: The bilateral fixed-angle plate and cannulated lag screws with anterior tension wiring preserved a constantly reduced fracture gap over 10,000 tensile cycles in contrast to modified anterior tension wiring, which exhibited significant widening of the gap after initial loading. Results of in vitro testing indicate that bilateral fixed-angle plates provide sustainable fixation stability offering a promising new option in the treatment for transverse patella fractures. © 2012 Springer-Verlag.
CRIS-Team Scopus Importer:2022-07-20
Keywords: Biomechanical stability; Fixed-angle patella plate; Patella fracture; Tension wiring